Agenda: Ormond Beach Task Force - California Coastal Conservancy (California Coastal Conservancy)
1. Welcome and Introductions, 2. Wetland Restoration Pland & Land Preservation Status, 3. Snowy Plover & Least Tern Recovery Program, 4. Gateway Park grants potential, ETC.